Le récit graphique et la narratologie contemporaine - Bene, Adrián (Acta Romanica Quinqueecclesiensis : La publication du Département d’Études Françaises et Francophones, Université de Pécs, 2025)
This study explores the mutual enrichment of narratology and comics studies over recent decades, focusing on how theories of narrative have expanded to include visual and multimodal forms. It traces the evolution from classical structuralist narratology to postclassical approaches that integrate cognitive, contextual, and transmedial perspectives. Central to the discussion is how graphic narratives challenge traditional notions of narration, focalization, and temporality by combining visual and verbal storytelling. The paper analyzes key contributions from scholars such as David Herman, Jared Gardner, Jan Baetens, and Karin Kukkonen, who emphasize the medium-specific features of sequential art. Concepts like closure, visual focalization, and multimodality are shown to parallel and transform earlier narratological categories. The study highlights the interdisciplinary bridges between cognitive science, semiotics, and visual studies in examining comics as narrative media. It also considers how graphic narratives redefine narrativity itself, suggesting that sequentiality may represent the minimal condition of narrative. Particular attention is given to the tension between linearity and simultaneity, the coexistence of description and narration, and the interplay of human and non-human perspectives. The paper concludes that graphic narrative theory not only applies narratology to a new medium but also reformulates its foundational concepts.